The Application of the Lymphoma International Prognostic Index to Predict Venous Thromboembolic Events in Diffuse Large B-Cell Lymphoma Patients - Abdel-Razeq, Hikmat; Ma’koseh, Mohammad; Abdel-Razeq, Rashid; Amarin, Rula; Abufara, Alaa; Mansour, Razan; Manasrah, Mohammad; Al-Rwashdeh, Mohammad; Bater, Rayan (Frontiers in Oncology, 2021)
BACKGROUND: Venous thromboembolic events (VTE) are commonly encountered in patients with lymphoma. Several risk assessments models (RAM) had attempted to identify higher risk patients with varying success. The International Prognostic Index (IPI) is a clinicopathological tool developed to help predict both response to treatment and prognosis of patients with diffuse large B-cell lymphoma (DLBL). OBJECTIVE: In this study, we utilize the IPI index to identify group of patients with DLBL at higher risk for VTE. PATIENTS/METHODS: Patients with pathologically-confirmed diagnosis of DLBL and with image-confirmed VTE, treated and followed at our institution were included. Rates of VTE was calculated for each risk category. RESULTS: A total of 373 patients, median age 49 (range: 18-90) years were included. VTE were reported in 56 (15.0%) patients; 51 (91.1%) had active disease while 29 (51.8%) were ambulatory at time of VTE diagnosis. VTE rates were particularly high among patients with poor performance status (26.2%, P=0.028) and high LDH (19.0%, P=0.023). Applying the age-adjusted IPI separated patients into two risk categories; VTE were diagnosed in 9.7% in patients with “low and low-intermediate” scores compared to 19.8% in patients with “high and high-intermediate” scores, P=0.020. CONCLUSIONS: The original IPI and its modified versions, routinely used at diagnosis as a prognostic and predictive tool for patients with DLBL, can also be utilized to define high risk patients for VTE; the risk of whom might be high enough to recommend thromboprophylaxis even in the ambulatory settings. More work is needed to refine and improve currently available RAMs.